Domain-general but not speech-specific auditory duration perception predicts pseudoword reading in adults - Batista, Ana Rita; Catronas, Dinis; Sousa, José; Folia, Vasiliki; Torres, Nathercia Lima; Silva, Susana (Frontiers in Human Neuroscience, 2023)
Associations between reading performance and duration perception have been found both for domain-general and speech-specific duration perception. However, research seems limited to children and, critically, the predictive value of the two duration perception modalities has not been compared so far. In the present study we compared the weight of domain-general (comparison of time intervals defined by beeps) vs. speech-specific duration perception (pre-attentive EEG responses to consonants with different durations) as statistical predictors of reading in a sample of 46 neurotypical adults (18-43 years old) with 13 years of schooling on average. Reading included word and pseudoword decoding, as well as reading comprehension. We ran one regression model with domain-general and speech-specific duration perception as predictors for each of the three reading skills. Pseudoword decoding was the only reading skill that was significantly predicted by duration perception, and this happened for domain-general duration perception only. A complementary analysis adding 26 typically developing and 24 dyslexic adults to the main sample (n = 96 in total) showed the same pattern of results in dyslexics, but not in added controls. Our findings strengthen the idea that duration perception is important to phonological encoding and its use in grapheme-tophoneme conversion, given that only pseudoword decoding was predicted by the interval comparison task. The irrelevance of speech-specific duration perception tones down the possibility that accurately perceiving the length of speech sounds is crucial to skilled reading.